The Function of Dialogue in Ivan Bunin’s Short Stories (Pragmatic Analysis) - Dimitruk, Elena; Titik Indarti; Resdianto Permata Raharjo (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research analyzes the function of dialogue in Ivan Bunin’s short stories. The analysis identifies the purposes for which dialogue is used, including strengthening character relationships, conveying social and cultural values, and referencing symbolic or philosophical contexts. Understanding the role of dialogue in a pragmatic context allows readers to interpret the deeper meaning of character interactions, providing insights into the intricate world created by Bunin. Using a descriptive qualitative method and a pragmatic analysis approach, this study examines how dialogue contributes to Bunin’s storytelling. The conclusion highlights the significance of this research in deepening our understanding and appreciation of Bunin’s literary artistry, as well as the ethical and aesthetic considerations intertwined with his works.